Djarum Foundation dengan Dinas Pendidikan Pemuda dan Olahraga Kabupaten Kudus Dalam Kerangka Corporate Social Responsibility (CSR) - Indra Diki Dewantara; Ahmad Taufiq; Suwanto Adhi (Journal of Politic and Government Studies, 2015)
At first, the concept of CSR is motivated by the company in its motivation charity. Its implementation in the form of assistance to the poor communities surrounding the company in the form of money or the manufacture of means of transport. Then the CSR concept evolved with emphasis on community empowerment program or better known as community development (CD). In the context of CSR, the CD's success is measured by the increase in quality of life in sekitarnya. One of the activities is to involve local communities to work within the company. Or by creating a new business in accordance with the capacity of local communities. In contrast to the condition of Indonesia, here the corporate social responsibility activities began only in recent years. The demands of society and the development of democracy as well as the swift currents of globalization and the free market, which raises awareness of the industry on the importance of implementing corporate social responsibility. As this study aims to determine the model partnership what exists between the Ministry of Youth and Sports Kudus and Djarum Foundation and aid delivery mechanisms Djarum Foundation Corporate Social Responsibility (CSR). In partnership awakened Djarum Foundation was incorporated as a private institution providing assistance to the pattern of Corporate Social Responsibility (CSR) or Corporate Responsibility Social. Factor of production area which is in the PT Djarum Kudus Regency is the key factor why Djarum Foundation focuses of development in the area of origin in order to compete with other regions. Where one is to optimize development efforts in the field of vocational education on the level of cooperation with the Ministry of Youth and So the results of this partnership can be felt directly by the school as an educational space that will provide learning to students in order to become a vocational school graduates are ready to use. In the course of this partnership, both private public institutions is equally have an important and strategic position and serve to complement the needs of each other. Ministry of Youth and Sports Kudus Regency serves as a mediator and facilitator to provide information about SMK needed Djarum Foundation, as well as Djarum Foundation serves as the provider and the owner of the resource which can make a significant contribution to the advancement of education in vocational shaded by the Ministry of Youth and Sports Kudus District.